Submitting sample, catalogue, specification,TDS and financial offer for the work of supply & installation of type of ceiling as counter proposal of the imprint concrete slab (henna ceiling) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the submission of technical & financial offer for counter proposal of henna ceiling of BRACU new campus project.